Hamilton Echelle Spectrograph Observations of Solar Analog Field Stars: Lithium Abundance and Activity - Dan Lubin; Bradford P. Holden; Camille Stock; Carl Melis; David Tytler (The Astronomical Journal, 2024)
We measured lithium (Li) abundance and instantaneous chromospheric Ca ii HK activity in Hamilton Echelle Spectrograph observations of 211 solar analog field stars, with one objective being potential identification of grand minimum candidates for ongoing multiyear observation. At the zero-age main sequence, Li abundance for a typical late-type dwarf begins at the local interstellar medium abundance and over the main sequence lifetime is steadily depleted by convection at a rate dependent on details of the star’s convection and mixing processes. Our Li abundance measurements show an overall decrease in Li abundance with age and effective temperature, consistent with earlier surveys. In our activity measurements, 41 stars show log R ′ _HK ≤ −5.0, which can be considered very inactive. Of the very inactive stars closest to solar effective temperature, 24 show Li abundances within the range typically observed for midlife Sun-like stars. Another three show very low Li abundance, which, combined with the low activity, suggest an older main sequence star or a slightly evolved star. We suggest that the combination of relatively undepleted Li and instantaneous very low activity might make these stars promising candidates for long time-series observations to determine if they are in a grand minimum state. The Hamilton Echelle Spectrograph observations are publicly available for download and are potentially useful for a variety of survey tasks involving Sun-like stars.